2020
DOI: 10.21203/rs.3.rs-38381/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data quality of the routine health management information system at the primary healthcare facility and district levels in Tanzania

Abstract: Background: Effective planning for disease prevention and control requires accurate, adequately-analysed, interpreted and communicated data. In recent years, efforts and investments have been put in strengthening health management information systems (HMIS) in Sub-Saharan Africa to improve data accessibility to decision-makers. This study assessed the quality of routine HMIS data at primary healthcare facility (HF) and district levels in Tanzania. Methods: The assessment involved Outpatient, Inpatient, Antenat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…Aggregated summary data from these reports is entered manually in the electronic DHIS2 at district level [6] where various users can view this summary data at different levels of aggregation (figure 1 b below). While the system is well established, incompleteness and inconsistency of data due to calculation and reporting errors have been described [7][8][9][10]. Also, digital aggregated data is often not available on time for decision making especially at sub-national level [11].…”
Section: Introductionmentioning
confidence: 99%
“…Aggregated summary data from these reports is entered manually in the electronic DHIS2 at district level [6] where various users can view this summary data at different levels of aggregation (figure 1 b below). While the system is well established, incompleteness and inconsistency of data due to calculation and reporting errors have been described [7][8][9][10]. Also, digital aggregated data is often not available on time for decision making especially at sub-national level [11].…”
Section: Introductionmentioning
confidence: 99%
“…22 These revelations were consistently conveyed in the outcomes of updated studies conducted by Mboera et al in Tanzania, and Kebede, Adeba et al in Ethiopia. 19,21,23 Besides, these findings cause PRISM's concepts more confirmable. Although in this study the HMIS data quality was not directly linked with other organizational factors (e.g.…”
Section: Discussionmentioning
confidence: 88%
“…This similar situation was also found in recent studies from different countries; Tanzania, Ethiopia, and Rwanda. [18][19][20] Besides, this study reported 100% timeliness coverage. This figure is consistent with the national report timeliness rate (97%) in Myanmar in 2017, but highly different from the report timeliness rates in a Myanmar study of Saw et al and an Ethiopian study of Ouedraogo et al at 50% and 70% respectively.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These differences may be partly attributed to the fact that the epidemiological week calendar year does not exactly align with the monthly calendar year. In addition, it is also likely that the larger differences observed in low, moderate and high epidemiological strata were due to data quality issues affecting reporting in the health facilities with high disease burden, [30] since data extraction entails an additional workload and time. Finally, there were periods of lower weekly reporting completeness between 2020 and 2021 that possibly suggest there was an issue with eIDSR data transmission as opposed to failure by the health facilities in sending the weekly reports.…”
Section: Discussionmentioning
confidence: 99%